A thematic analysis of Palahniuk’s fiction in light of Epicureanism - Hesamoddin Shahriari; Ghazal Toosi (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2017)
Chuck Palahniuk is a contemporary American writer whose novels have been adapted into acclaimed Hollywood motion pictures. Palahniuk’s literary style is often branded as modernist with nihilistic undertones. In spite of such views, in this article, we argue that through a close reading of Palahniuk and a critical interpretation of the recurrent themes in his novels, one can find traces of Epicurean philosophy echoed through the ages. Though different in means, both Palahniuk and Epicurus seem to highlight the importance of and the strive for achieving a state of ataraxia through overcoming fear and aponia through transcending physical pain and torment. After providing an introduction to Epicurean thought and Palahniuk’s style and works, connections will be established between the various shared elements and themes